2010
DOI: 10.1109/tdei.2010.5412010
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic view of aging mechanism of polyimide film under pulse voltage in presence of partial discharge

Abstract: Inverter-fed motors are damaged due to pulse voltage. The situation leads to early failure of insulation. Polyimide is an important insulating material in the inverter-fed motors. Its insulation aging process and failure mechanism are different from traditional ac and dc voltage. In this paper, structure change of polyimide film aging under pulse voltage above partial discharge inception voltage (PDIV) is investigated through scanning electron microscopy (SEM), thermally stimulated current (TSC) and lifetime t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…In these works, molecular chain scissions were found to occur on the polymer surface and to generate polymer radicals. These evolutions in samples may indicate that the deterioration of insulation is severe and may extend from surface, considering the translucent nature of the material [38]. They may be often accompanied by extensive deterioration in the mechanical properties of the materials, such as tensile strength, impact strength and elongation, all of which are important parameters in the performance of an insulating material.…”
Section: Termination Stepmentioning
confidence: 99%
“…In these works, molecular chain scissions were found to occur on the polymer surface and to generate polymer radicals. These evolutions in samples may indicate that the deterioration of insulation is severe and may extend from surface, considering the translucent nature of the material [38]. They may be often accompanied by extensive deterioration in the mechanical properties of the materials, such as tensile strength, impact strength and elongation, all of which are important parameters in the performance of an insulating material.…”
Section: Termination Stepmentioning
confidence: 99%
“…Recently, Zha et al found that nano-TiO 2 particles could improve the dielectric strength, lifetime, and space charge characteristics based on the dielectric properties tests of PI/TiO 2 nanocomposites 19 20 . Zhou et al attributed the enhanced corona resistance of PI nanocomposites to the high charge transport capacity of nanostructure based on the corona-aging and breakdown tests under high frequency square wave pulses 21 24 . However, most of the researches focus on the comparison between pure PI and nanocomposites at the same temperature.…”
mentioning
confidence: 99%
“…The dissipation time under higher frequency is longer. 4. For the fluorinated sample, the surface charge density is lower and decays much faster than that of the unfluorinated one under the same conditions.…”
Section: Discussionmentioning
confidence: 85%
“…Serdyuk et al investigated charging of polymer surfaces by means of impulse corona discharges and concluded that charge deposition was different in case of glow corona and burst corona [3]. Wu et al studied the structure change of polyimide film aging under pulse voltage and found that the degradation of structure in polyimide propagates from surface to interior with continuous aging [4]. The surface charge distribution of PTFE insulators under impulse voltage was measured and analyzed by Wang et al and it was found that micro-discharge was the prerequisite of the surface charge accumulation [5].…”
Section: Introductionmentioning
confidence: 99%